Composite wheat-amaranth flour baking properties and bread freshness - Mykolenko, Svitlana; Миколенко, Світлана Юріївна; Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Dudin, Volodymyr; Дудін, Володимир Юрійович (IOP Conference Series, 2023)
The study has reviled the benefits of amaranth groat flour application into wheat bread making towards enhancing the technological efficiency and the quality of the bread, prolonging the freshness of the product without artificial improvers involved in the formulations. Paying attention to textural characteristics of the wheat-amaranth bread during its shelf-life, amaranth groat flour as a derived product of amaranth grain processing presented a positive impact on the change of textural properties of the bread crumb during wheat-amaranth bread shelf-life. The effect of ranging 5–30% substitution of common wheat high-grade flour by the amaranth flour derived from partially defatted amaranth grain was investigated and the complex organoleptic quality of the bread made of the composite flour reached the highest level at 15% of the amaranth flour in the formulation. The technological parameters of bread making such as the duration of proofing, shape stability, specific volume, crumb porosity, baking and drying losses, when wheat high-grade flour was partially replaced by the amaranth grain-derived milling product showed better performance for the bread enriched by the amaranth flour at higher substitution level approving the wider application of the pseudocereal flour in the food industry. The freshness of the bread made of the composite flour is related to the textural characteristics of the crumb which tend to change drastically due to styling. The amaranth groat flour application into the wheat bread formulation led to changes in compressive force and tension of the crumb, the stress value at relative strain ε = 25%, the elastic modulus, and the statical elastic hysteresis index. The resulting application of the amaranth groat flour into bread formulation allowed to ensure a 2-2.5-fold increase in the freshness of wheat bread with a 15% amaranth groat flour content when providing higher comprehensive quality of the product. У дослідженні засуджено переваги застосування борошна з амарантової крупи у виробництві пшеничного хліба для підвищення технологічності та якості хліба, продовження свіжості продукту без використання штучних покращувачів у рецептурах. Зважаючи на текстурні характеристики пшенично-амарантового хліба протягом терміну зберігання, борошно з амарантової крупи як похідний продукт переробки зерна амаранту позитивно вплинуло на зміну текстурних властивостей м’якушки хліба протягом терміну зберігання пшенично-амарантового хліба. . Досліджено вплив заміни 5–30 % борошна вищого ґатунку м’якої пшениці на амарантове борошно, отримане з частково знежиреного зерна амаранту, і комплексна органолептична якість хліба із композитного борошна досягла найвищого рівня – 15 % від амарантового борошна в рецептурі. Технологічні показники приготування хліба, такі як тривалість розстоювання, формостійкість, питомий об’єм, пористість м’якушки, втрати на випікання та сушіння, при частковій заміні пшеничного борошна вищого ґатунку продуктом помелу із зерна амаранту показали кращі показники для хліба. збагачений амарантовим борошном на вищому рівні заміни, що схвалює ширше застосування псевдозернового борошна в харчовій промисловості. Свіжість хліба, виготовленого із композитного борошна, пов’язана з текстурними характеристиками м’якушки, які мають тенденцію різко змінюватися через формування. Внесення борошна з крупи амаранту в рецептуру пшеничного хліба призвело до зміни сили стиснення та розтягу м’якушки, величини напруження при відносній деформації ε = 25 %, модуля пружності та показника статичного пружного гістерезису. Отримане застосування борошна з крупи амаранту в рецептуру хліба дозволило забезпечити підвищення свіжості пшеничного хліба в 2-2,5 рази з вмістом борошна з крупи амаранту 15% при забезпеченні вищої комплексної якості продукту.
Хлібопекарські властивості композиту пшенично-амарантового борошна та свіжість хліба
Keywords: amaranth groats; амарантова крупа; wheat bread; пшеничний хліб; properties; властивості; composition; склад; rheology; реологія